DEVELOPMENT MODEL OF SUPPLY CHAIN MANAGEMENT IN MANUFACTURING PROCESSES - Waluyo, Minto; Huda, Syamsul (Acta Scientiae et Intellectus, 2024)
The researchers developed a model of supply chain management (MSC) for snack marketing as a strategy in competition. This research process was conducted in three experiments, i.e. measurement models, structural models and modification models. The results of the mathematical equation of supply chain management model development is Y5 = 0.23 X + Z5. The hypothesis results are all of the MSC variables influence significantly with Goodness of Fit Indices.